2022
DOI: 10.1002/prop.202200077
|View full text |Cite
|
Sign up to set email alerts
|

Who's Afraid of the Supersymmetric Dark? The Standard Model vs Low‐Energy Supergravity

Abstract: Use of supergravity equations in astronomy and late-universe cosmology is often criticized on three grounds: (i) phenomenological success usually depends on the supergravity form for the scalar potential applying at the relevant energies; (ii) the low-energy scalar potential is extremely sensitive to quantum effects involving very massive particles and so is rarely well-approximated by classical calculations of its form; and (iii) almost all Standard Model particles count as massive for these purposes and none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 89 publications
3
24
0
Order By: Relevance
“…Progress on these questions may be facilitated by recently developed tools in coupling non-supersymmetric matter to supergravity [912,913,914,915,916,917]. This has been initiated in [918], where evidence was found that the supergravity form of the action -and a small splitting in the gravity supermultiplet -is stable against integrating out heavy, non-supersymmetric particles, thanks to the interplay with auxiliary fields associated with gravity, the goldstino and other supermultiplets in the supersymmetric gravity sector. Having a gravity sector that is supersymmetric down to low energies, coupled to a visible sector where supersymmetry is non-linearly realised, is also motivated by the fact that gravity would have the weakest couplings to any supersymmetry breaking sector [455].…”
Section: Branes Extra Dimensions and String Symmetriesmentioning
confidence: 99%
“…Progress on these questions may be facilitated by recently developed tools in coupling non-supersymmetric matter to supergravity [912,913,914,915,916,917]. This has been initiated in [918], where evidence was found that the supergravity form of the action -and a small splitting in the gravity supermultiplet -is stable against integrating out heavy, non-supersymmetric particles, thanks to the interplay with auxiliary fields associated with gravity, the goldstino and other supermultiplets in the supersymmetric gravity sector. Having a gravity sector that is supersymmetric down to low energies, coupled to a visible sector where supersymmetry is non-linearly realised, is also motivated by the fact that gravity would have the weakest couplings to any supersymmetry breaking sector [455].…”
Section: Branes Extra Dimensions and String Symmetriesmentioning
confidence: 99%
“…Crucially, their presence changes the way that UV physics can enter into the low-energy potential; because supersymmetry-breaking masses necessarily themselves involve F the contribution of virtual heavy nonsupersymmetric states to the lowenergy potential tends to be δV ∝ M 2 F +h.c. (where M is the UV scale) rather than directly as an F -independent term like δV ∝ M 4 [21]. Even though M 4 eventually arises once F is integrated out, the form involving F shows that the most UV-sensitive effective couplings have a reduced dimension.…”
Section: Jcap03(2022)064mentioning
confidence: 99%
“…Ref. [21] explores more concretely why generic potentials are consistent with the above supergravity form, using this general framework. When supersymmetry is nonlinearly realized (as it must be in such theories) there is always a low-energy superfield X that is nilpotent, X 2 = 0, since this is what is required to represent the goldstino [34], and it is typically true that W X = 0 for this field.…”
Section: Jcap03(2022)064mentioning
confidence: 99%
See 1 more Smart Citation
“…We consider it safer to include the loop effects as corrections to the Kahler potential, and then to study the minima of the resulting supergravity scalar potential. The validity of such an approach, even concerning loops with fields below the SUSY breaking scale, has recently been emphasized in [54].…”
Section: Support By Feynman-diagram Calculationsmentioning
confidence: 99%